What Counts? Sources of Knowledge in Children's Acquisition of the Successor Function. Issue 4 (21st January 2021) - Schneider, Rose M.; Sullivan, Jessica; Guo, Kaiqi; Barner, David
Abstract : Although many U.S. children can count sets by 4 years, it is not until 5½–6 years that they understand how counting relates to number—that is, that adding 1 to a set necessitates counting up one number. This study examined two knowledge sources that 3½‐ to 6‐year‐olds ( N  = 136) may leverage to acquire this "successor function": (a) mastery of productive rules governing count list generation; and (b) training with "+1" math facts. Both productive counting and "+1" math facts were related to understanding that adding 1 to sets entails counting up one number in the count list; however, even children with robust successor knowledge struggled with its arithmetic expression, suggesting they do not generalize the successor function from "+1" math facts.